Effect of Plant Growth Regulators on Growth and Yield of Daisy (Aster amellus L.) Cv. Dwarf Pink - Y C Raveendra (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2013)
An experiment was carried out to improve plant stature in daisy (Aster amellus L.) cv. Dwarf Pink using various growth regulators. Among the various growth promoters and their combinations tested, gibberellic acid (150ppm) and brassinosteroid (0.5ppm) application produced maximum vegetative growth, spike yield and vase-life. It is concluded that a combination of gibberellic acid (150ppm) and BR (0.5ppm) is helpful improving growth and quality in daisy cv. Dwarf Pink.